INTERNALISASI NILAI-NILAI MODERASI BERAGAMA MELALUI PERAN GURU PENDIDIKAN AGAMA ISLAM DI SMP AL-FURQON JEMBER - Sinta Amilia Asfarina; Sofyan Rofi; Dhian Wahana Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Religious moderation is one of the important pillars in maintaining the harmony of the life of the pluralistic Indonesian people. This study aims to examine in depth how Islamic Religious Education (PAI) teachers internalize the values of religious moderation to students at Al-Furqon Junior High School Jember. Using a descriptive qualitative approach through in-depth interviews, participatory observations, and documentation studies, this study identifies three main dimensions of the role of PAI teachers, namely as value educators, role models of moderate character, and facilitators of tolerance habituation. The findings of the study show that the cultivation of moderation values is carried out through the integration of PAI materials with local wisdom, the application of the Discussion-Based Worksheet-based discussion method (LKBD), and the example of teachers in daily interactions. The positive impacts that can be seen include the formation of tolerance, the increase of balanced religious awareness, and the creation of a harmonious school environment. This study also highlights that the success of internalizing the value of religious moderation is greatly influenced by the quality of teacher examples, school cultural support, and integration between religious values and national values. The implications of this research are relevant for education policy developers in designing a PAI curriculum that is more adaptive to Indonesia's diversity. Keywords: religious moderation, PAI teachers, internalization of values, tolerance, Al-Furqon Junior High School Jember